2019
DOI: 10.3389/fpubh.2019.00270
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Marginally Housed Youth: Prevalence and Risk Factors

Abstract: Objective: Homeless and marginally housed youth are particularly vulnerable members of society, and are known to experience numerous health problems, including psychiatric illness, substance use, and viral infection. Despite the presence of these risk factors for cognitive compromise, there is limited research on the cognitive functioning of homeless and marginally housed youth. The present study examines the degree and pattern of cognitive impairment and associations with key risk factors in a sample of margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…below the normative mean to define scores that fall within the clinically impaired range on a given test, in accord with existing guidelines 26 and with other studies in homeless people. 7,12…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…below the normative mean to define scores that fall within the clinically impaired range on a given test, in accord with existing guidelines 26 and with other studies in homeless people. 7,12…”
Section: Methodsmentioning
confidence: 99%
“…below the normative mean to define scores that fall within the clinically impaired range on a given test, in accord with existing guidelines 26 and with other studies in homeless people. 7,12 A history of traumatic brain injury was ascertained using a structured medical history questionnaire and defined as the occurrence of at least one injury to the head associated with any duration of loss of consciousness, confusion and/or memory loss, or neuroradiological evidence of trauma on whole brain images collected on a 3T Phillips Achieva scanner, or evidence of persistent sequelae attributable to injury (for example seizures, need for anticonvulsants, organic personality disorder). We adopted an inclusive definition of traumatic brain injury by grouping individuals as either having a history based on the above criteria, or no history, a previously used approach.…”
Section: Clinical Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Homeless and precariously housed youth and young adults may have differential risk factors and health outcomes and represent a uniquely vulnerable demographic within this marginalized population. 4,5 Although not formally homeless, individuals who live in precarious housing (e.g., shelters, single-room occupancy hotels, rooming houses) have comparable mortality, chronic health conditions, and unmet health care needs. 6,7 Over half of homeless and precariously housed individuals have a history of traumatic brain injury (TBI), and approximately one-fifth have a history of moderate or severe TBI.…”
mentioning
confidence: 99%
“…Study context. Studies have shown that homelessness is associated with several risk factors for developing cognitive disorders, such as traumatic brain injuries [4,23], neurodevelopmental issues [24,25], or alcohol consumption [26,27], and that the prevalence of cognitive disorders is higher in people experiencing homelessness [11,28]. Although research into mental disorders in homeless people has been carried out in France [29][30][31], there is a lack of data for cognitive disorders specifically from a French population.…”
Section: Study Settingsmentioning
confidence: 99%